Modelling and controlling the process of cutting with complex-geometry tools to improve efficiency of mining machines and plants - Mikhailov Stanislav (EDP Sciences, 2021)
Constant quality improvement through automation of production processes is an important prerequisite for increased viability of mining machines and plants. Factors that limit the automation of the cutting machining operations include the problem of controlling the chip formation and chip crushing. Solution of this problem necessitates theoretical description of the material cutting conditions for tools with curvilinear surfaces. The paper describes basic principles of modeling the cutting process using complex-geometry tools with curvilinear rake. The theory is based on the concept of chip formation as a process of inhomogeneous strain in the plastic zone where the chip originates. Based on the analysis of the stress-strain state in the cutting zone, criterial relationships were derived that correlate the geometric parameters of the chip shape and machining conditions of the curvilinear-rake tool. Prerequisites for chip breaking are stability of the chip shape during cutting, stable chip-to-obstacle contact, high chip stiffness and low flexibility. The machining conditions leading to chip fragmentation could be found by solving the strength problem. Through establishing the cause-and-effect relationships of the processes of chip formation, curling and breaking, new approaches to achieving favorable chip shape may be found by exerting deliberate impact on the plastic zone of the chip formation through optimizing the conditions for the chip flow off the tool. The established relationships between the output parameters of the cutting process and process conditions of cutting with a complex-geometry tool offer the way to control the chip flow parameters in various machining operations. The research is aimed at creating scientifically informed design codes and optimization of cutting parameters for tools with curvilinear chip-curling and chip-breaking rake surfaces.